KEMAMPUAN PEMAHAMAN KONSEP DENGAN MODEL PEMBELAJARAN MAKE A MATCH - Lisa Elmiana; Kashardi Kashardi (Jurnal Math-UMB.EDU, 2016)
This research is motivated by the importance of students' understanding of mathematical concepts to learning mathematics. Therefore, it is necessary to use a model that is capable of learning to improve students' understanding of mathematical concepts one of which is a cooperative learning model make a match. This study aims to determine the activity of students and teachers in the learning process and to determine the improvement of students' comprehension of mathematical concepts using cooperative learning model make a match. This study was conducted on 10 April to 10 May 2014 in the Junior High School 13, the city of Bengkulu. Research subjects of this study were all students of class VII C to determine the increase in activity and the ability of understanding the concept of using observation sheets of students and teachers to see what students and teachers during the learning process, then performed a pre-test to determine the ability of beginning students and post-test to determine the ability of the student understanding of mathematical concepts as applied to cooperative learning model make a match on each cycle. BasedÂ  results of data analysis it can be concluded that an increase in student activity, the activity of the teacher in the learning process and the increasing ability of understanding mathematical concepts students each cycle.Keywords:understanding the concept, make a match